Effective leadership in startups - Khan, Adam (2019)
We time and again stumble on word such as, ‘Leader’ ‘Leadership’ ‘Qualities a Leader must have’ the world over. The word leadership and the qualities a leader must possess in order to be an effective leader at workplace but then how many times we hear leader fall apart and turn into a boss or a manager that we then turn ourselves away from. I believe, we didn’t quite get that right, or did we? for me “leadership is like a ghost, on whom, everyone talks about but only few have seen it. There is hardly any particular discussed or analysed papers around on ‘Effective Leadership in a Startup environment’. A topic seems to be a little tickly and isn’t quiet straightforward as one might have thought though. Being a leader to me is essentially whole lot more than just being in charge of a business or people, there is a lot more at stake and it quiet cut out just for everyone.